Prevalence and Persistence of Multidrug-Resistant Yersinia enterocolitica 4/O:3 in Tonsils of Slaughter Pigs from Different Housing Systems in Croatia - Nevijo Zdolec; Marta Kiš; Dean Jankuloski; Katerina Blagoevska; Snježana Kazazić; Marina Pavlak; Bojan Blagojević; Dragan Antić; Maria Fredriksson-Ahomaa; Valerij Pažin (: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations, 2022)
Yersinia enterocolitica is one of the priority biological hazards in pork inspection. Persistence of the pathogen, including strains resistant to antimicrobials, should be evaluated in pigs from different housing systems for risk ranking of farms. In this 2019 study, tonsils were collected from 234 pigs, of which 69 (29.5%) were fattened on 3 big integrated farms, 130 (55.5%) on 10 medium-sized farms, and 35 (15%) on 13 small family farms. In addition, 92 pork cuts and minced meat samples from the same farms were tested for the presence of Y. enterocolitica using the culture method. Phenotypic and genetic characteristics of the isolates were compared with previously collected isolates from 2014. The overall prevalence of Y. enterocolitica in pig tonsils was 43% [95% CI 36.7–49.7]. In pigs from big integrated, medium-sized, and small family farms, the prevalence was 29%, 52%, and 40%, respectively. All retail samples of portioned and minced pork tested negative for pathogenic Y. enterocolitica, likely due to high hygienic standards in slaughterhouses/cutting meat or low sensitivity of culture methods in these matrices. The highest recovery rate of the pathogen from tonsils was found when alkali-treated PSB and CIN agar were combined. The biosecurity category of integrated and medium farms did not affect the differences in prevalence of Y. enterocolitica (p > 0.05), in contrast to family farms. Pathogenic ail-positive Y. enterocolitica biotype 4 serotype O:3 persisted in the tonsils of pigs regardless of the type of farm, slaughterhouse, and year of isolation 2014 and 2019. PFGE typing revealed the high genetic concordance (80.6 to 100%) of all the Y. enterocolitica 4/O:3 isolates. A statistically significant higher prevalence of multidrug-resistant Y. enterocolitica 4/O:3 isolates was detected in the tonsils of pigs from big integrated farms compared to the other farm types (p < 0.05), with predominant and increasing resistance to nalidixic acid, chloramphenicol, and streptomycin. This study demonstrated multidrug resistance of the pathogen in pigs likely due to more antimicrobial pressure on big farms, with intriguing resistance to some clinically relevant antimicrobials used in the treatment of yersiniosis in humans.
Keywords: Yersinia enterocolitica 4/O:3; pigs; slaughter; farm; antimicrobial resistance